2013
DOI: 10.1152/ajprenal.00431.2012
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressin inhibits apoptosis in renal collecting duct cells

Abstract: The peptide hormone arginine vasopressin (AVP) plays a critical role in regulating salt and water transport in the mammalian kidney. Recent studies have also demonstrated that AVP can promote cell survival in neuronal cells through V1 receptors. The current study addresses whether AVP can inhibit apoptosis in kidney collecting duct cells via V2 receptors and also explores the downstream signaling pathways regulating this phenomenon. Terminal deoxynucleotidyl transferase-mediated dUTPbiotin nick-end labeling an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 46 publications
4
20
0
Order By: Relevance
“…1), which is to be expected given that the binding is mediated by the BH4 domain (residues 34 -39). However, it is likely that the two forms will have different properties, since full-length (23 kDa) Bok can be phosphorylated at Ser 8 (37), which is absent from the 21-kDa form. The region to which Bok binds appears to be a flexible, unstructured, surface-exposed loop within the ARM3 domain of IP 3 Rs (14,16).…”
Section: Discussionmentioning
confidence: 99%
“…1), which is to be expected given that the binding is mediated by the BH4 domain (residues 34 -39). However, it is likely that the two forms will have different properties, since full-length (23 kDa) Bok can be phosphorylated at Ser 8 (37), which is absent from the 21-kDa form. The region to which Bok binds appears to be a flexible, unstructured, surface-exposed loop within the ARM3 domain of IP 3 Rs (14,16).…”
Section: Discussionmentioning
confidence: 99%
“…AVP can inhibit apoptosis through V2Rs and downstream cAMP-mediated pathways in the mammalian kidney (77). In rats with elevated AVP levels, it has been found that kidney cell proliferation is unaffected by selective V1a or V1b receptor antagonists.…”
Section: Distribution and Function Of V2rsmentioning
confidence: 99%
“…In addition to these endocrine functions, AVP also contributes to regulating mitogenesis, cell survival, and death (apoptosis) (77).…”
mentioning
confidence: 99%
“…In this study, the results showed that AVP might be such a molecule connecting neuronal cell damage with myocyte damage. Although AVP has been shown to inhibit apoptosis in renal collecting duct cells (Miller et al, 2013), its mechanisms in cardiac survival and damage are unknown. Other potential molecules and mechanisms linking stroke and cardiac cell death also need to be explored including systemic inflammatory responses (Kostulas et al, 1998;Mo et al, 2013), neuroendocrine-mediated myocardial suppression (Oppenheimer and Hachinski, 1992;Wira et al, 2011), changes in circulating endothelial progenitor cells (Paczkowska et al, 2013) as well as the blood-brain barrier integrity.…”
Section: Discussionmentioning
confidence: 99%